Patients Perception and Utilization of Integrated Services in Embu Referral Hospital, Kenya. - Githae, Caroline N.; Matiang'i, Micah; Muraya, Moses (International Journal of Innovative Research in Information Security (IJIRIS), 2019)
Globally, there are approximately 36.7 million people living with HIV, with an estimated 3.8 million individuals newly infected with HIV and about 5,000 new infections per day in the year 2017-2018. Integration of HIV treatment with primary care services improves effectiveness, efficiency and equity in service delivery. In Embu teaching and referral hospital, integration of HIV services with other primary health services were initiated in 2014 and up to date, the integration has not been fully adopted by the clients therefore, the study sought to establish the perception of seropositive clients on integrated HIV and primary health care services in Embu Teaching and Referral hospital. A cross sectional survey design was used to collect data from a sample of 302 sero positive clients who were selected using simple random method. A structured and semi-structured questionnaire was used to collect quantitative data while key informant interviews (KII) and Focus Group Discussions (FGDs) helped to collect qualitative data. The tools were reliable at cronbach’s alpha of 0.817 SPSS version 23 was used to analyze the data. Qualitative data from focused group discussions and key informant questionnaire was analysed thematically and theme summaries given under each theme. A binary logistic regression model was used to predict the effect of other determinants of utilization of integrated HIV services and primary health care services. Results: Majority of the respondents (59.6%) were aged over 35 years with majority being female (58.9%) and the married were 57.6% of the total sample. On perception on integrated services 76.5% had a positive perception. Conclusion: Majority of the clients had a positive perception towards the integrated service. They perceived the staff attitude as positive and acknowledged that integration allowed them opportunities to share their life experiences. However, they felt there was need to increase services provided under the integrated arrangement such as cancer screening, TB clinics and other services such as blood pressure monitoring. Recommendation: The Government of Kenya through the Ministry of Health should engage the county government and support from NGO`s to come up with structures and resources needed to expand the facility in terms of facility space and incorporation of other primary health care services like cancer screening, diabetes screening, dental and ophthalmology services
©2019 This is an open access article distributed under the terms of the Creative Commons Attribution License, Which Permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited
Keywords: Perception; integrated services; Embu teaching and referral hospital; HIV patients; primary health care services